Ripple effect in regional housing and land markets in Iran: implications for portfolio diversification - Gholipour, Hassan F.; Lean, Hooi Hooi (International Journal of Strategic Property Management, 2017)
In recent years, real estate has become a very popular investment choice for Iranian investors due to several interrelated economic and political reasons. The purpose of this study is to find out how real estate investors can gain diversification benefits from investing within the real estate sector across provinces of Iran. We use semi-annual data from selected provinces of Iran over the period of 1993–2014 and apply univariate Lagrange multiplier unit root tests with one and two structural breaks to the ratio of the provincial to national house and residential land prices respectively. We find diversification benefit can be gained by investing in housing markets across provinces because house prices in half of the sample provinces tend to drift away from house prices in the rest of the country. In addition, our results show that it is difficult to create an adequately diversified portfolio in a residential land market because shocks to the residential land prices of provinces ripple out across the nation. These findings should be valuable to domestic and foreign investors who are interested in the Iranian real estate sector, especially after the lifting of several international economic sanctions.First published online 29 Sep 2017